What Determines the Reservation Wages of Unemployed Workers? : New Evidence From German Micro Data - Prasad, Eswar (IMF Working Papers; Working Paper ;, 2003)
This paper provides new empirical evidence on the relationship between reservation wages of unemployed workers and macroeconomic factors--including the unemployment rate and generosity of the unemployment compensation system--as well as individual-specific determinants, such as human capital proxies and length of unemployment spell. The longitudinal dataset provides an interesting perspective on how reservation wages change over time and how they correlate with accepted wage offers for workers who move from unemployment to employment. The findings shed light on the disincentive effects of the German tax and transfer system for the employment decisions of unemployed workers at different skill levels.